2012
DOI: 10.1007/s11661-012-1393-0
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Grain Boundary Planes in Interstitial Free Steel

Abstract: The grain boundary character distribution in a commercial IF steel has been measured as a function of lattice misorientation and boundary plane orientation. The grain boundary plane distribution revealed a relatively low anisotropy with a tendency for grain boundaries to terminate on low index planes having relatively low surface energy and large interplanar spacings. Although the most common grain boundary plane orientation was (111), grain boundaries terminated on higher index planes were sometimes found. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 26 publications
6
24
1
1
Order By: Relevance
“…The average distribution of these three macroscopic parameters (x, r ˘ ) of grain boundary is again inferred to be of random type. Similar results of such random distribution have been reported in fully ferritic microstructures [27][28][29].…”
Section: Rotation Axis Distributionsupporting
confidence: 88%
“…The average distribution of these three macroscopic parameters (x, r ˘ ) of grain boundary is again inferred to be of random type. Similar results of such random distribution have been reported in fully ferritic microstructures [27][28][29].…”
Section: Rotation Axis Distributionsupporting
confidence: 88%
“…[3,4] The purpose of this paper is to review and compare the grain boundary character distributions of four microstructures processed in different ways. These distributions have been previously reported in different contexts, [3,5,6] but here we focus on the role of the transformation path on the grain boundary character distribution.…”
Section: Introductionmentioning
confidence: 52%
“…Here, the typical c-fiber texture was observed having a texture strength of~12 MRD (Figure 4(c)). It has been [3], [5], and [6], respectively.…”
Section: A the Role Of Thermomechanical Route On The Grain Boundary mentioning
confidence: 99%
“…Recent experimental characterization of steels has shown that several of these symmetric tilt grain boundaries are observed at a concentration higher than random grain boundaries. 64,65 For example, Beladi and Rollett quantified that the R3(112) symmetric tilt grain boundary is observed at >10 multiples of a random distribution (MRD) of grain boundaries, 64,65 i.e., much larger than would be expected. While the experimental observation of h100i symmetric tilt grain boundaries (R5, R13 GBs) is below 1 MRD, these grain boundaries are commonly used in DFT studies due to the low periodic distances required in the grain boundary plane.…”
Section: Methodology a Grain Boundariesmentioning
confidence: 99%